2015
DOI: 10.1007/s00125-015-3767-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid development of cardiac dysfunction in a canine model of insulin resistance and moderate obesity

Abstract: Aims/hypothesis The worldwide incidence of obesity and diabetes continues to rise at an alarming rate. A major cause of the morbidity and mortality associated with obesity and diabetes is heart disease, yet the mechanisms that lead to cardiovascular complications remain unclear. Methods We performed cardiac MRI to assess left ventricular morphology and function during the development of moderate obesity and insulin resistance in a well-established canine model (n=26). To assess the influence of dietary fat c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 47 publications
3
25
0
1
Order By: Relevance
“…Previously published findings after six weeks in each diet condition reported that plasma insulin was significantly increased from baseline from 50.4 ± 7.7 to 60.4 ± 10.7 pmol/L in LARD animals, whereas the SO intervention caused no significant changes in insulin (34.6 ± 6.8 to 31.0 ± 4.3 pmol/L) . Similarly, in these longer studies, we found that LARD feeding, but not SO feeding, induced plasma hyperinsulinemia at basal insulin levels in both artery and vein (Figure A‐B).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Previously published findings after six weeks in each diet condition reported that plasma insulin was significantly increased from baseline from 50.4 ± 7.7 to 60.4 ± 10.7 pmol/L in LARD animals, whereas the SO intervention caused no significant changes in insulin (34.6 ± 6.8 to 31.0 ± 4.3 pmol/L) . Similarly, in these longer studies, we found that LARD feeding, but not SO feeding, induced plasma hyperinsulinemia at basal insulin levels in both artery and vein (Figure A‐B).…”
Section: Resultssupporting
confidence: 85%
“…The acute effects of 6 weeks of LARD and SO diets on SI and cardiac function have been reported previously . The present study reports data on extended diet durations of 3.0 ± 0.3 months of LARD feeding and 3.9 ± 0.1 months of SO feeding.…”
Section: Methodssupporting
confidence: 75%
“…Rather than attempting such direct comparisons, a more synergistic interpretation may be helpful. Two theories clearly extend from the work by Broussard et al [21] in concert with other recent human and animal investigations: (1) using appropriately sensitive measurement techniques, such as motion-sensitive MRI, cardiac mechanics of the LV are impaired in the setting of obesity; and (2) insulin resistance is a critical element—at least as one of several potentially causative or intermediary factors—in the linkage between obesity and heart disease. The immediate knowledge gaps that extend from these theories are then fairly straightforward: (1) what is the long-term prognostic significance of reduced cardiac mechanics in obese patients; and (2) can therapeutically targeting insulin signalling pathways positively impact the adverse effects of obesity on the heart?…”
Section: Reconciling Human and Animal Diseasementioning
confidence: 77%
“…In the current issue of Diabetologia , Broussard et al add to this collective experience with animal models of obesity and contribute interesting new insights [21]. Using a canine model of moderate obesity induced by lard-based high-fat feeding, the authors observed LV systolic dysfunction (i.e.…”
Section: Insights From Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation